The standardized extract of Centella asiatica and its fractions exert antioxidative and anti-neuroinflammatory effects on microglial cells and regulate the Nrf2/HO-1 signaling pathway - Hambali, Aqilah; Jusril, Nor Atiqah; Md Hashim, Nur Fariesha; Abd Manan, Nizar; Adam, Siti Khadijah; Mehat, Muhammad Zulfadli; Adenan, Mohd Ilham; Stanslas, Johnson; Abdul Hamid, Hafizah (IOS Press, 2024)
Background: Neuroinflammation and oxidative stress can aggravate the progression of Alzheimer's disease (AD). Centella asiatica has been traditionally consumed for memory and cognition. The triterpenes (asiaticoside, madecassoside, asiatic acid, madecassic acid) have been standardised in the ethanolic extract of Centella asiatica (SECA). The bioactivity of the triterpenes in different solvent polarities of SECA is still unknown. Objective: In this study, the antioxidative and anti-neuroinflammatory effects of SECA and its fractions were explored on lipopolysaccharides (LPS)-induced microglial cells. Methods: HPLC measured the four triterpenes in SECA and its fractions. SECA and its fractions were tested for cytotoxicity on microglial cells using MTT assay. NO, proinflammatory cytokines (TNF-α, IL-6, IL-1β), ROS and MDA (lipid peroxidation) produced by LPS-induced microglial cells were measured by colourimetric assays and ELISA. Nrf2 and HO-1 protein expressions were measured using western blotting. Results: The SECA and its fractions were non-toxic to BV2 microglial cells at tested concentrations. The levels of NO, TNF-α, IL-6, ROS and lipid peroxidation in LPS-induced BV2 microglial cells were significantly reduced (p<0.001) by SECA and its fractions. SECA and some of its fractions can activate the Nrf2/HO-1 signalling pathway by significantly enhancing (p<0.05) the Nrf2 and HO-1 protein expressions. Conclusion: This study suggests that the inhibitory activity of SECA and its fractions on pro-inflammatory and oxidative stress events may be the result of the activation of antioxidant defence systems. The potential of SECA and its fractions in reducing neuroinflammation and oxidative stress can be further studied as a potential therapeutic strategy for AD.